Symbiotic efficiency of native and exotic rhizobium strains nodulating lentil (Lens culinaris Medik.) in soils of southern Ethiopia - Tena, W.; Woldemeskel, Endalkachew; Walley, F. (MDPI, 2016)
Lentil plays a major role in the food and nutritional security of low income Ethiopian families because of the high protein content of their seed; however, their productivity typically is low largely due to soil fertility limitations. Field and pot experiments were conducted during the 2011 cropping season to determine the effectiveness of Rhizobium strains on two cultivars of lentil in Southern Ethiopia. Six rhizobial inoculant treatments (four indigenous and two commercial inoculants), a nitrogen (N) fertilizer treatment (50 kg·urea·ha−1) and an absolute control (non-inoculated non-fertilized) were used. Inoculated plants produced significantly higher nodule number, nodule dry weight, grain yield and yield components than non-inoculated non-fertilized plants. Inoculation of field grown lentil with rhizobia strain Lt29 and Lt5 enhanced seed yield by 59% and 44%, respectively. Whereas urea fertilization enhanced yields by 40%. Similarly, grain yields were increased during the pot experiment by 92% and 67% over the control treatments by inoculation with Lt29 and Lt5, respectively. The highest levels of N fixation were achieved in plants inoculated with Lt29 (65.7% Ndfa). Both field and pot investigations indicate that inoculation of lentil with native rhizobial strains replace the need for inorganic N fertilization to optimize lentil yields.